2016
DOI: 10.1108/jme-03-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Hip-hop based interventions as pedagogy/therapy in STEM

Abstract: Purpose This paper aims to argue that providing youth of color with opportunities to explore content while reflecting on and sharing mental health concerns is an under-focused dimension of teaching and learning that has the potential to positively impact these students’ academic achievement in science, technology, engineering and mathematics (STEM) disciplines Design/methodology/approach This paper used a qualitative study to interrogate a teaching/learning model through a hip-hop-based science program. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
1
21
0
6
Order By: Relevance
“…Notably, Hill reported this did not benefit their wellbeing in isolation from the educational setting, but also helped students and teachers imagine new, culturally relevant possibilities for engaging in classroom spaces. Emdin et al (2016) also reported mental health benefits in connection to classroom practice and learning. These benefits included students' ability to gain deeper knowledge of themselves by engaging with, expressing, and sharing issues they face in their daily lives through lyric composition.…”
Section: Educational Interventionsmentioning
confidence: 98%
See 4 more Smart Citations
“…Notably, Hill reported this did not benefit their wellbeing in isolation from the educational setting, but also helped students and teachers imagine new, culturally relevant possibilities for engaging in classroom spaces. Emdin et al (2016) also reported mental health benefits in connection to classroom practice and learning. These benefits included students' ability to gain deeper knowledge of themselves by engaging with, expressing, and sharing issues they face in their daily lives through lyric composition.…”
Section: Educational Interventionsmentioning
confidence: 98%
“…This included recognition of Hip Hop as originating in the Bronx, New York (DeCarlo & Hockman, 2004) in the 1970s, among African American and Latino (Gonzalez & Hayes, 2009) or inner-city youth (Boutin-Foster et al, 2010). Many also acknowledged the different elements of Hip Hop culture (Boutin-Foster et al, 2010;Emdin et al, 2016;Gonzalez & Hayes, 2009;Harris et al, 2012;Sussman et al, 1995). These were described variously as b-boying/breaking/dance/movement, graffiti/tagging/art/visual art, DJing; MCing/rap/rapping, music/sound, dress/clothing style, language/slang, and knowledge of self.…”
Section: Description and Positioning Of Hip Hopmentioning
confidence: 99%
See 3 more Smart Citations